Substitution of limestone for eggshell powder in the diet of Japanese laying quails - Moura, Glenda Roberta Silva; Reis, Renata de Souza; Mendonça, Michele de Oliveira; Salgado, Hallef Rieger; Abreu, Karine da Silva; Madella, Gabriela dos Santos; de Lima, Michele Bernardino [UNESP] (FapUNIFESP (SciELO), 2020)
Were evaluated the effects of substituting limestone with quail eggshell powder on the zootechnical performance, egg quality, and economic efficiency of Japanese quails during peak egg production (11-20 weeks old). The experimental period was 63 days, divided into three 20-day periods. A completely randomized experimental design was used with five treatments (0, 25, 50, 75, and 100% substitution of limestone by eggshell powder), six repetitions, and seven birds per experimental unit, for a total of 210 quails. Feed intake, production of egg/bird/day, egg production per bird housed, marketable egg production, egg viability, feed conversion per egg mass, Seedor index, tibia calcium content, and percentage of calcium excreted were determined. The following variables for egg quality were analyzed: egg weight, specific weight, percentage of egg yolk, albumen and shell, and shell thickness. Economic efficiency was evaluated in fresh and industrialized eggs. Statistical analyses were performed using the SAS software, version 9.2 (2010). Substitution of limestone for eggshell powder had no significant effect on zootechnical performance, tibia calcium content, or egg quality. However, there were significant effects on the percentages of albumen and calcium excreted. The substitution of limestone by eggshell powder in quail feed resulted in higher economic efficiency indexes. These results indicate that the use of 100% eggshell powder in the feed of Japanese laying quails is viable.
Keywords: Calcium content; Seedor index; Zootechnical performance